Licensing of Organotin Antifouling Paint Pest Control Applicators in Florida - Frederick M. Fishel (EDIS)
PI-152, a 4-page fact sheet by Frederick M. Fishel, explains the licensing and regulation of persons who apply restricted use organotin antifouling paints in Florida. Published by the UF Pesticide Information Office, April 2007.